PSYCHOLOGICAL DISTRESS AMONG MOTHERS OF CHILDREN WITH EMOTIONAL AND BEHAVIORAL PROBLEMS DURING COVID-19 PANDEMIC IN MALAYSIA - Masiran, Ruziana; Ibrahim, Normala; Awang, Hamidin; Lim, Poh Ying (Malaysian Journal of Public Health Medicine, 2022)
The spread of COVID-19 and its subsequent social distancing measures carried a significant psychological burden on many parents worldwide. This study was done to determine the prevalence and factors associated with psychological distress experienced by mothers of children with emotional and behavioral problems (EBP) during the lockdown period in Malaysia. An online survey using purposive sampling technique was conducted. Psychological distress was determined by DASS-21 scores. Prevalence of stress, anxiety, and depressive symptoms among mothers of children with EBP during the pandemic in Malaysia was 36.4%, 43.6%, and 30.9%, respectively. Mothers with a total monthly income of ? RM 999 were 25 times more likely to have stress symptoms (OR = 25.275, 95% CI = 1.17 – 547.41) and ten times more likely to have depressive symptoms (OR = 10.289, 95% CI = 1.17 – 90.88). Mothers with lower incomes are more psychologically vulnerable to the pandemic impact.